Behaviors of Safe Bike Riding Among Student Khamthaleso Wittaya School Kham Thaleso District, Nakhon Ratchasima Province - Kunlayanee, (Primary Health Care Journal (Northeastern Edition), 2021)
This research is a cross-sectional descriptive study and aimed to study the behaviors of safe bike riding among students at Khamthaleso Wittaya school, Kham Thaleso district, Nakhon Ratchasima province. The sample is students studying at Khamthaleso Wittaya school traveling by motorcycle were 284 people. Data were collected by questionnaire. Descriptive data were analyzed by descriptive statistics such as frequency percentage and standard deviation, and Independent samples t-test. The results showed that the sample group had a low level of overall safe motorcycle driving behavior at ( =2.27, SD.=0.81), classified by side, it was found that In terms of caution in driving, there is a low level of safety at ( =2.37, SD.=0.73), followed by traffic compliance with a low level of safety at ( =2.34, SD=0.78), and in terms of checking the condition of the motorcycle, there is a low level of safety at ( =2.10, SD.=0.92). The results of the comparison of differences in safe motorcycle driving behaviors revealed that gender, motorcycle riding experience engine size, and distances that are regularly used differently There are different safe motorcycling behaviors. statistically significant at (P-value<0.05). The educational level and age are different. There is no difference in the behavior of safe riding motorcycles.